INTERAKSI SOSIAL KERJASAMA ANTAR PANITIA PADA ACARA PERNIKAHAN MELAYU SAMBAS DI DESA SERANGGAM - Hayati, Nandung; Noor, Agus Sastrawan; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This study aims to determined the social interaction of cooperation between committees at Malayness Sambas wedding ceremony in Seranggam village. The research method used was qualitative approach descriptive form. The object of his research was a member of the wedding committee in Seranggam village, amounting to 10 people. Technique of collecting data was done by observation, interview, and documentary. While the data collection tool were an observation guide, interview guide, and documentation. The result of the research showed that the social interaction of cooperation between marriage committees had been running in accordance with the existing social interaction process. This is seen from the cooperation of mutual cooperation between committees such as activities at the meeting of the establishment of wedding committee, the day of nunjam tarup, making spices as well as nyarro 'k, antarpakatan and the big day. Another thing that was encountered is cooperation in the form of co-optation such as members of the committee to openly accept opinions and decided through deliberation, accepting every policy and direction of the new committee chairman on the day of making tarub until the wedding is over.Keywords: Social Interaction, Cooperation, Malayness Sambas Marriage